CT Imaging Biomarkers Predict Clinical Outcomes After Pancreatic Cancer Surgery - Zhu, Liang; Shi, Xiaohua; Xue, Huadan; Wu, Huanwen; Chen, Ge; Sun, Hao; He, Yonglan; Jin, Zhengyu; Liang, Zhiyong; Zhang, Zhuoli (Medicine (Baltimore), 2016)
This study aimed to determine whether changes in contrast-enhanced computed tomography (CT) parameters could predict postsurgery overall and progression-free survival (PFS) in pancreatic cancer patients. Seventy-nine patients with a final pathological diagnosis of pancreatic adenocarcinoma were included in this study from June 2008 to August 2012. Dynamic contrast-enhanced (DCE) CT of tumors was obtained before curative-intent surgery. Absolute enhancement change (AEC) and relative enhancement change (REC) were evaluated on DCE-CT. PFS and overall survival (OS) were compared based on CT enhancement patterns. The markers of fibrogenic alpha-smooth muscle antigen (α-SMA) and periostin in tumor specimens were evaluated by immunohistochemical staining. The χ test was performed to determine whether CT enhancement patterns were associated with α-SMA-periostin expression levels (recorded as positive or negative). Lower REC (<0.9) was associated with shorter PFS (HR 0.51, 95% CI: 0.31-0.89) and OS (HR 0.44, 95% CI: 0.25-0.78). The α-SMA and periostin expression level were negatively correlated with REC (both P = 0). Among several CT enhancement parameters, REC was the best predictor of patient postsurgery survival. Low REC was associated with a short progression-free time and poor survival. The pathological studies suggested that REC might be a reflection of cancer fibrogenic potential.